Water-Energy-Food Nexus in Large Asian River Basins - Olli Varis (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
The connections between water, food and energy are currently being discussed more than ever before, thanks to the recently emerged concept of the water-energy-food security nexus. Various organizations and authors have defined and addressed the concept from their own view points: nexus is, indeed in the air. This Special Issue looks at the water-energy-food security nexus in the context of large Asian river basins, with a focus on transboundary rivers shared by several countries. The articles included in the Special Issue analyse what benefits the nexus approach could bring to these kinds of, often quite demanding, settings. And where are the potential pitfalls that call for further development. The thematic areas covered in the Special Issue thus include water resources management; energy planning and policies with an emphasis on hydropower; and food production systems, including fisheries, irrigation and cropland management. Due to its focus on transboundary contexts, the articles also look at the geopolitical, international cooperation and security aspects related to the nexus. The articles of the Special Issue include case studies from relevant transboundary river basins, with a focus on the Mekong River Basin in Southeast Asia as well as the river basins in Central Asia. Articles also include a comparative analysis in several large Asian river basins as well as more theoretical discussions of the water-energy-food security nexus and its linkages to other framings and approaches, such as IWRM and sustainable development.